2018
DOI: 10.1111/1759-7714.12771
|View full text |Cite
|
Sign up to set email alerts
|

Practical value of identifying circulating tumor cells to evaluate esophageal squamous cell carcinoma staging and treatment efficacy

Abstract: BackgroundThis study was conducted to investigate the correlation between clinicopathological features and post‐therapeutic response in esophageal squamous cell carcinoma (ESCC) patients. Peripheral blood circulating tumor cells (CTCs) expressing epithelial‐mesenchymal transition markers were identified.MethodsPeripheral blood samples were collected from 71 patients with newly diagnosed ESCC and 40 healthy volunteers. CTCs were isolated using CanPatrol CTC enrichment technology. RNA‐fluorescent in situ hybridi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 32 publications
1
13
0
Order By: Relevance
“…CTCs are derived from primary or metastatic lesions, and metastasis begins with epithelial-mesenchymal transition (EMT). Chen et al (41) and Han et al (42) demonstrated the importance of the EMT process in tumor metastasis and CTC production; however, CTC clusters, also known as microemboli, were not detected in any of the cohorts enrolled in these studies (41,42). Clustered cancer cells in the blood have been reported to serve as an indicator of poor prognosis and early recurrence in lung cancer (43,44), and high malignancy in breast cancer (30,45); however, to the best of our knowledge, they have not been studied in ESCC.…”
Section: Discussionmentioning
confidence: 90%
“…CTCs are derived from primary or metastatic lesions, and metastasis begins with epithelial-mesenchymal transition (EMT). Chen et al (41) and Han et al (42) demonstrated the importance of the EMT process in tumor metastasis and CTC production; however, CTC clusters, also known as microemboli, were not detected in any of the cohorts enrolled in these studies (41,42). Clustered cancer cells in the blood have been reported to serve as an indicator of poor prognosis and early recurrence in lung cancer (43,44), and high malignancy in breast cancer (30,45); however, to the best of our knowledge, they have not been studied in ESCC.…”
Section: Discussionmentioning
confidence: 90%
“…One such study assessing the clinical relevance of epithelial, mesenchymal and epithelial-mesenchymal CTCs in colorectal cancer found that only mesenchymal and epithelial-mesenchymal CTCs, not epithelial CTCs, correlated with clinical stage and metastasis [13]. Similarly, mesenchymal CTCs in esophageal squamous cell carcinoma have been shown to denote clinical stage and treatment efficacy [14]. These findings support the importance of isolating mesenchymal CTCs for inclusion in downstream analysis.…”
Section: Current Use Of Ctcsmentioning
confidence: 81%
“…A total of ten studies were enrolled for the PFS analysis of 822 EC patients [ 13 , 25 , 26 , 27 , 29 , 54 , 75 , 84 , 86 , 87 ]. In this cohort, the average age was 63.3 years (61.5–66) and the median CTC positivity rate was 46.2% (18.0–79.7).…”
Section: Resultsmentioning
confidence: 99%